Cultural distance and the performance of international joint ventures: a critical assessment of model specifications and variable measurement. (1st January 2013) - Christoffersen, Jeppe; Globerman, Steven; Nielsen, Bo Bernhard
This study provides a critical summary and assessment of the empirical literature on the relationship between cultural distance and the performance of international joint ventures (IJVs) based on studies published over the period 1993–2008. The existing literature reports inconsistent and largely statistically insignificant findings for the relationship. We add to this literature by analysing some 63 empirical studies of the cultural distance – IJV performance linkage. We further confirm the absence of any consistent and statistically significant linkage, despite strong conceptual arguments for anticipating a strong empirical relationship. We also evaluate different proposed explanations of the weak empirical findings in the literature and find some mixed support for these explanations. We conclude with some suggestions for improving the modelling of the cultural distance – IJV performance relationship.